2012
DOI: 10.1155/2012/960128
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B Inhibits ERK and p38 MAPK Signaling in TGF-β1-Stimulated Human Hepatic Stellate Cell Line (LX-2) via Distinct Pathways

Abstract: Salvianolic acid B (SA-B) is water-soluble component of Radix Salvia miltiorrhiza. The previous work indicated that SA-B can inhibit MAPK and Smad signaling in activated hepatic stellate cells (HSCs) to perform anti-fibrotic activity Lv et al. 2010. However, some studies have shown that there is cross-talk between MAPK and Smad in certain cell types. Thus, the anti-fibrotic action of SA-B may be through the cross-talk. In order to clarify the mechanism of SA-B further, we knocked down Smad in LX-2 cells (SRV4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…As with shRNA, delivery of non-native miRNA constructs have been used to suppress target protein expression in cell cultures [4][5][6]. In whole animal models [30,31], pioneering studies in the cancer field have described impressive therapeutic effects with these non-native miRNAs, yet the approach had not been tested in heart, in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with shRNA, delivery of non-native miRNA constructs have been used to suppress target protein expression in cell cultures [4][5][6]. In whole animal models [30,31], pioneering studies in the cancer field have described impressive therapeutic effects with these non-native miRNAs, yet the approach had not been tested in heart, in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent developments in RNA interference technologies (RNAi), it is highly anticipated that these viral-based delivery approaches can be extended for the suppression of target protein expression in the heart [3]. The approach has been overwhelmingly successful in isolated cell culture models [4][5][6], including several studies for the suppression of malic enzyme as targeted in this study [7][8][9]. However, there are only a few reports for successful suppression of a target protein in heart, in vivo, based on RNAi schemes [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the stem cells have the potential for therapy of liver diseases, but may also be involved in the formation of liver cancer (Rountree et al, 2012). Not long ago, Zhigang Lv.et.al concluded that TGF-β1could persistently activate ERK and p38MAPK signaling in HSCs (Lv and Xu, 2012). Now, deregulation of TGF-β signaling is acting as a molecular pathway to TISC-based malignancy (Rountree et al, 2012).…”
Section: Mapk and Liver Cancermentioning
confidence: 99%
“…Cardiac fibroblasts play a key role in cardiac function. As we all know, MMP-9 greatly influence the occurrence and development of cardiac remodeling [76]. One study about the catalytic MMP-9 CD (domain of MMP-9) and neonatal cardiac fibroblasts showed 200 nm MMP-9 CD can stimulate cardiac fibroblast migration; increase collagen synthesis; upregulate secretion of ICAM, TNF- α , IL-6 and VCAM-1; and downregulate the expression of VEGF.…”
Section: Cardiovascular Pharmacologymentioning
confidence: 99%